Yellow pigment of Metarhizium anisopliae and its application to the dyeing of fabrics. (30th April 2019) - Yan, Biaobiao; Yang, Muying; Zhou, Qingqing; Xing, Tieling; Chen, Guoqiang; Sheng, Jiayong
Abstract : Microbial dyes have received substantial attention because of their natural environmental protection, simple access, and reduced regional and seasonal restriction. In this work, a microbial dye, the yellow pigment produced by Metarhizium anisopliae, was first studied then applied. The strain produced by the culture was identified, and the conditions for producing yellow pigment were optimised. Further, the stability of M. anisopliae yellow pigment was examined, and the pigment was applied to the dyeing of silk and wool fabrics. The results showed that the homology of the strain with M. anisopliae was 99.98%. In liquid fermentation culture, the optimal carbon source was glucose, and the dosage was 30 g/l. The maximum pigment yield can be obtained by culturing with 4% v/v of inoculation quantity at pH 7 and 30 °C. In addition, the effects of pH, temperature and metal ions on the yellow pigment of M. anisopliae were significant. The optimum dyeing process conditions were dyeing temperatures of 80 °C for silk and 90 °C for wool, with a dyeing time of 60 min. This research developed a novel microbial dye and studied its application for the dyeing of protein fibres.